Cholinium-Based Ionic Liquids as Promising Antimicrobial Agents in Pharmaceutical Applications: Surface Activity, Antibacterial Activity and Ecotoxicological Profile - María Teresa García; Elena Bautista; Ana de la Fuente; Lourdes Pérez (MDPI AG, 2023)
Cholinium-based ionic liquids are compounds increasingly studied in pharmaceutics and biomedicine to enhance bioavailability in drug delivery systems and as bioactive ingredients in pharmaceutical formulations. However, their potential as antimicrobial agents has scarcely been investigated. Herein, we explored the antimicrobial activity of a series of surface-active cholinium-based ionic liquids (Chol-ILs). For this purpose, Chol-ILs with alkyl chains of 10-16 carbon atoms were synthesized and their self-assembly in aqueous medium was investigated. Subsequently, their antimicrobial activity against a panel of clinically relevant bacteria and their ability to eradicate MRSA and P. aeruginosa PAO1 biofilms was evaluated. Finally, we analyzed the ecotoxicological profile of Chol-ILs in terms of susceptibility to aerobic biodegradation and acute aquatic toxicity against D. magna and V. fisheri. Our results reveal that cholinium-based ILs with alkyl chain lengths ≥12 C show a broad spectrum of antibacterial activity. Their antimicrobial efficacy depends on their hydrophobicity, with the C14-C16 homologs being the most effective compounds. These ILs exhibit antimicrobial activity similar to that of imidazolium ILs and quaternary ammonium antiseptics. Moreover, the longer alkyl chain Chol-ILs are able to eradicate established biofilms at concentrations as low as 16-32 µg/mL. The biodegradation rate of cholinium-based ILs decreases with alkyl chain elongation. Our results reinforce the suitability of Chol-ILs as promising multifunctional compounds for application in pharmaceutical and biomedical formulation.